2021
DOI: 10.3389/fped.2021.643387
|View full text |Cite
|
Sign up to set email alerts
|

Investigation Into the Current Situation and Analysis of the Factors Influencing Extrauterine Growth Retardation in Preterm Infants

Abstract: Objective: This study aims to explore the occurrence of extrauterine growth retardation (EUGR) in preterm infants with a gestational age of <34 weeks, at discharge, and the factors influencing the occurrence of EUGR.Method: A retrospective analysis of 691 preterm infants with a gestational age of less than 34 weeks, born in our hospital over the past 3 years. At discharge, the growth indicators head circumference, weight, and length were used to divide the infants into an EUGR group (n = 255) and the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…We found that infants with maternal hypertension and SGA at birth were at an increased risk for PGF. These findings are consistent with previous study relating gestational hypertension and SGA to discharge weight, length, and head circumference being below the 10th percentile [31]. An important driver of preterm birth is hypertensive disorders including preeclampsia, which may lead to maternal vasoconstriction, insufficient placental blood flow, low fetal nutritional reserve, and intrauterine growth restriction.…”
Section: Discussionsupporting
confidence: 92%
“…We found that infants with maternal hypertension and SGA at birth were at an increased risk for PGF. These findings are consistent with previous study relating gestational hypertension and SGA to discharge weight, length, and head circumference being below the 10th percentile [31]. An important driver of preterm birth is hypertensive disorders including preeclampsia, which may lead to maternal vasoconstriction, insufficient placental blood flow, low fetal nutritional reserve, and intrauterine growth restriction.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, they have a high chance of requiring invasive mechanical ventilation and a long duration of hospital stay. This leads to an increased risk of hospital-acquired infections and a high incidence of necrotizing small-bowel colitis, which can lead to neonatal sepsis [30,31]. Our study found that in China, SEVs of short-gestation and low-birth-weight neonates decreased and then increased in both early and late-onset neonatal sepsis.…”
Section: Discussionmentioning
confidence: 59%
“…EUGR may impose long-term serious impact on the development of nervous and many other systems in premature newborns [ 28 ]. Previous studies have shown that gestational age <34 weeks, birthweight <1500 g, and SGA are independent risk factors for the development of EUGR in newborns [ 29 31 ]. However, our study did not find significant differences in these factors.…”
Section: Discussionmentioning
confidence: 99%